طرق تحديد مؤشرات عمل محركات الديزل البحرية أثناء تغير الشروط الخارجية - أحمد, معروف; يوسف, حسين صلاح (Latakia University Journal -Engineering Sciences Series, 2019)
يتضمن هذا البحث نتائج الدراسة التي أُجريت لتحديد تأثير تغيرات مؤشرات الوسط الخارجي (EMP) على الحالة الإجهادية والمؤشرات الاقتصادية (ECh) لمحركات الديزل البحرية المشحنة (CMDE) المستخدمة لدفع السفينة السورية "الأسد". استخدمت في هذا البحث أكثر الطرق المعتمدة عالمياً مثل: K.Cinner, DIN 6270, СIMAC, GOST 24.060.07 (بعد اتخاذ الإجراءات الخاصة لجعلها مناسبة للاستخدام في شروط منطقة شرق المتوسط (ERMS) حيث أُنجز هذا البحث). تمت مقارنة هذه النتائج مع نتائج تطبيق طريقة العالم "Vasiliev-Jugin" على المعطيات الإحصائية التي تم تجميعها خلال فترة استثمار السفينة المذكورة. في هذا البحث تم وضع ثوابت تصحيح وإنشاء مخططات بيانية بواسطة النموذج الرياضي الذي أُعدَّ في هذا البحث من أجل محركات الديزل (DE) المستخدمة لدفع السفن خلال إبحارها في ERMS. This research contains the results of a study, which has been done to determine the effect of external parameters (EMP) variation upon stress case, and economical characteristics (ECh) of charged marine diesel engines (CMDE) that are used to propel Syrian ship “Al-Assad”. The most international related methods as: K.Cinner, DIN 6270, CIMAC, GOST 24.060.07 had been used in this research (after making them suitable to use in eastern region of Mediterranean (ERMS) where this research had been done). These results had been compared with results that were obtained by applying “Vasiliev Jugin” method on the statistical data which are grouped during exploitation of that ship. In this research correction factors and histograms had been built by mathematical model which has been done in this research, for diesel engines (DE) that are used to propel ships during its navigation in ERMS.